2017
DOI: 10.1093/toxsci/kfx117
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Nlrp3 Is Required for Inflammatory Changes and Nigral Cell Loss Resulting From Chronic Intragastric Rotenone Exposure in Mice

Abstract: Complex interactions between genetic and environmental factors are widely believed to underlie the incidence and progression of Parkinson's disease (PD). Rotenone is a naturally occurring metabolic toxin employed as an insecticide and piscicide identified as a risk factor for the development of PD in agricultural workers. The Nlrp3 inflammasome is an intracellular mediator that can initiate an inflammatory cascade in response to cellular stress. Reports by others indicating that NLRP3 expression was detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 60 publications
8
44
0
Order By: Relevance
“…Our studies have been consistent with these reports [14], however, we also unexpectedly identified NLRP3 expression in a subset of surviving DA neurons in late stage PD patients and neuronal cell models [40]. Others report inflammasome activity in neurons [27, [49][50][51], but to our knowledge no in vivo studies have examined directly the function of NLRP3 in DA neurons in the context of aging.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our studies have been consistent with these reports [14], however, we also unexpectedly identified NLRP3 expression in a subset of surviving DA neurons in late stage PD patients and neuronal cell models [40]. Others report inflammasome activity in neurons [27, [49][50][51], but to our knowledge no in vivo studies have examined directly the function of NLRP3 in DA neurons in the context of aging.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to observing an increased number of GFAP-immunoreactive astrocytes associated with aging, we also observed significantly more astroglia in 18-month old animals expressing Nlrp3 L351P compared to animals expressing Nlrp3 WT and Nlrp3 A350V . We and others have previously reported astrocytes to be a direct target of IL-1b [14,[59][60][61] the canonical proinflammatory effector cytokine of the inflammasome [7], and others have previously reported evidence of neuronal IL-1b expression [62]. Analysis of SNpC tissues was consistent with these previous reports, demonstrating easily observable IL-1b expression in TH-immunoreactive fibers ( Supplementary Figure 2).…”
Section: Sds-page and Western Blottingsupporting
confidence: 87%
See 2 more Smart Citations
“…Studies of the past 5 years have shown that a cause of the degeneration is inflammatory attack of dopaminergic neurons of the substantia nigra by microglia when their NLRP3 inflammasome is activated by phagocytized misfolded α-synuclein. [1][2][3][4][5][6][7][8][9][10][11][12] The misfolded β-sheet-rich α-synuclein aggregates in PD's hallmark Lewy bodies. If misfolded α-synuclein templates the misfolding of more synuclein, it constitutes a PD-propagating prion.…”
Section: Introductionmentioning
confidence: 99%